Peningkatan Kualitas Pembelajaran Bahasa Arab pada Tingkat Madrasah Diniyah Tanwirul Futuh Kabupaten Pasuruan - Nur Hasan; Moh Muslim (Institute for Research and Community Service (LP2M), Universitas Negeri Malang, 2021)
This community service activity aims to improve the quality of Arabic learning for Madin teachers so that students are more motivated and active in the learning process. The form of implementing community service is in the form of training and mentoring in the use of Arabic language learning methods and strategies so that the learning process is more active and varied and not boring. The implementation of this community service uses the PRA (Participatory Rural Appraisal) method, by prioritizing the participation of madin teachers in improving the quality of Arabic learning and providing ongoing assistance. The results of community service activities include: (1) Strengthening Arabic learning strategies based on innovative, creative Arabic learning methodologies through socialization and training; (2) Mentoring that is carried out intensively every two months of learning Arabic has produced results, as evidenced by the enthusiasm of the students increasing during the learning process; (3). There is a need for continuous mentoring of madin teachers in learning Arabic so that learning is of higher quality. Kata kunci— Bahasa Arab, Guru Madin, Kualitas Pembelajaran, Pemberdayaan Abstract This community service activity aims to improve the quality of Arabic learning for Madin teachers so that students are more motivated and active in the learning process. The form of implementing community service is in the form of training and mentoring in the use of Arabic language learning methods and strategies so that the learning process is more active and varied and not boring. The implementation of this community service uses the PRA (Participatory Rural Appraisal) method, by prioritizing the participation of madin teachers in improving the quality of Arabic learning and providing ongoing assistance. The results of community service activities include: (1) Strengthening Arabic learning strategies based on innovative, creative Arabic learning methodologies through socialization and training; (2) Mentoring that is carried out intensively every two months of learning Arabic has produced results, as evidenced by the enthusiasm of the students increasing during the learning process; (3). There is a need for continuous mentoring of madin teachers in learning Arabic so that learning is of higher quality. Keywords— Arabic, Madin Teachers, Quality of Learning, Empowerment